Regional Disparities of Stunted Toddler in Indonesia - Ina Kusrini1 , Agung Dwi Laksono2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Although there has been a decline in the prevalence of stunting in Indonesia in the past decade, the figure is still the highest among countries in Southeast Asia. The purpose of the study was to analyze the regional disparity of stunted toddlers in Indonesia. The analysis in this study uses data from the 2017 Indonesian Nutritional Status Monitoring. The sample used in this study was 149,571 toddlers aged 0-59 months. Data were analyzed using the Binary Logistic Regression test. Toddlers in the Sumatra region have the possibility of 0.921 times stunted compared to toddlers in the Papua region. The Java-Bali region was 0.805 times more likely than toddlers in the Papua region to be stunted. The Nusa Tenggara Region was 1.39 times more likely than toddlers in the Papua region to be stunted. Kalimantan Region has 1.161 times more likely than toddlers in the Papua region to be stunted. The Sulawesi region has 1.18 times the possibility of toddlers in the Papua region being stunted. Maluku region has a probability of 0.88 times that of toddlers in the Papua region to be stunted. There was a regional disparity of stunted toddler in Indonesia.